Can theory-driven implementation interventions help clinician champions promote opioid stewardship after childbirth? Protocol for a pragmatic implementation study - Michelle H. Moniz; Michelle H. Moniz; Michelle H. Moniz; Amy M. Kilbourne; Amy M. Kilbourne; Alex F. Peahl; Alex F. Peahl; Alex F. Peahl; Jennifer F. Waljee; Jennifer F. Waljee; Jennifer F. Waljee; Shelytia Cocroft; et al. (Frontiers in Global Women's Health)
BackgroundOur objective is to determine the effect of a new national clinical practice guideline (CPG) for pain management after childbirth, as implemented with less vs. more intensive implementation support, on postpartum opioid prescribing.MethodsA quasi-experimental analysis will measure the impact of post-childbirth pain management guidelines on opioid prescribing in a statewide hospital collaborative, overall and among key patient subgroups at risk for inequitable care and outcomes. We will also use a randomized, non-responder design and mixed-methods approaches to evaluate the effects of Replicating Effective Programs (REP), a theory-driven, scalable implementation intervention, and Enhanced REP (E-REP; i.e., REP augmented with facilitation, which is individualized consultation with site champions to overcome local barriers) on the uptake of the CPG. The study will include hospitals within the Obstetrics Initiative (OBI), a perinatal collaborative quality initiative funded by Blue Cross Blue Shield of Michigan that includes 68 member hospitals serving more than 120,000 postpartum people, over approximately 15 months. Hospitals not initially responding to REP—defined by performance <15th percentile of all OBI hospitals for (a) inpatient order for opioid-sparing postpartum pain management (e.g., scheduled acetaminophen and non-steroidal anti-inflammatory drugs when not contraindicated), or (b) amount of opioid prescribed at discharge—will be allocated via block randomization to continue REP or to E-REP. Using interrupted time series analyses, the primary analysis will evaluate the rate of postpartum opioid-sparing prescribing metrics at the time of discharge (primary outcome) and opioid prescription refills and high-risk prescribing (secondary outcomes) before and after CPG implementation with REP. We will evaluate inequities in outcomes by patient, procedure, prescriber, and hospital factors. Exploratory analyses will examine temporal trends in patient-reported outcomes and the effects of continued REP vs. E-REP among slower-responder sites. We will evaluate implementation outcomes (e.g., acceptability, feasibility, costs, needed REP and E-REP adaptations) using clinician and patient surveys and qualitative methods (ClinicalTrials.gov identifier: NCT06285123).DiscussionFindings will inform refinements to the REP and E-REP interventions and add to the literature on the effectiveness of facilitation to promote uptake of evidence-based clinical practices in maternity care.